Regional empowerment through tuberose-based MSME product innovation and appropriate technology in Doplang Village - Mega Novita; Senowarsito Senowarsito; Rifki Hermana; Sutomo Sutomo (Universitas Muhammadiyah Magelang, 2024)
The community service program under the Regional Empowerment (PW) scheme aims to enhance economic capacity and community welfare through local product innovation based on appropriate technology (AT). Doplang Village in Semarang Regency has significant potential in cultivating tuberose, which is integrated into micro, small, and medium enterprises (MSMEs) with the support of AT. This innovation distinguishes local MSME products from existing market offerings through the application of technologies such as Solar Cell Battery Storage Systems, packaging tools, social media branding, and formulations for products like soap and hand sanitizer. The program was implemented through workshops, training sessions, and intensive mentoring, focusing on developing skills in product development, management, and marketing. Pre-test and post-test evaluations showed a significant improvement of over 50 points in participants’ skills and knowledge, particularly in management and product innovation. The program resulted in six main products, including baby oil, perfume, hand sanitizer, and laundry soap, contributing to local economic growth and supporting sustainable tourism through diversification of tuberose-based products and the application of renewable energy.